INCREASING STUDENT LEARNING OUTCOMES ON CIVICS EDUCATION WITH COOPERATIVE LEARNING MODEL WITH TALKING STICK TYPE IN GRADE FOURTH ELEMENTARY SCHOOL - Nurul Fajri; Arifmiboy (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The purpose of this study is to describe the improvement of student learning outcomes in PKn learning with Cooperative Learning model with Talking Stick type in Grade Fourth Public Elementary School Number 01 Bandar Buat. The approach used is qualitative and quantitative. The subjects were  teacher and 30 students. The results of this study indicate improvement in student learning outcomes. In cycle I obtained the average percentage of student learning outcomes 81 and on the  cycle II is 89. Thus, cooperative model type Talking Stick can improve student learning outcomes in learning Civics in class IV SD Negeri 01 Bandar Buat.